Analysis Variation Paddle Wheel With Photovoltaic Form Cultivation with Consumption Electricity - Sahat Sitompul; Winfrontstein Naibaho; Welmar Olfan Basten Barat (Politeknik Negeri Batam, 2023)
The main problem that is often found in the failure of microalgae production is poor water quality during the maintenance period. One of the causes of deteriorating water quality is the lack of oxygen which endangers microalgae which can inhibit cell growth so that it can reduce its productivity. On this basis, efforts are needed to refresh the water or aeration to help increase the dissolved oxygen (DO) level in the microalgae growth container using a paddle wheel. The development of an aerator blade design that has optimum efficiency is needed to reduce high electricity consumption and see more effective cell growth.